Strength training and shoulder proprioception - Salles, J. I.; Velasques, B.; Cossich, V.; Nicoliche, E.; Ribeiro, P.; Amaral, M. V.; Motta, G. (Journal of Athletic Training, 2015)
Context: Proprioception is essential to motor control and joint stability during daily and sport activities. Recent studies demonstrated that athletes have better joint position sense (JPS) when compared with controls matched for age, suggesting that physical training could have an effect on proprioception.